2017
DOI: 10.1155/2017/7259014
|View full text |Cite
|
Sign up to set email alerts
|

Tests and Analyses of Slotted-In Steel-Plate Connections in Composite Timber Shear Wall Panels

Abstract: The authors present an experimental and analytical study of slotted-in connections for joining walls in the Masonite flexible building (MFB) system. These connections are used for splicing wall elements and for tying down uplifting forces and resisting horizontal shear forces in stabilizing walls. The connection plates are inserted in a perimeter slot in the PlyBoard™ panel (a composite laminated wood panel) and fixed mechanically with screw fasteners. The load-bearing capacity of the slotted-in connection is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, contrary to previous studies, [20][21][22][23] Foliente et al's numerical study 4,26 concluded that TSWs do not impact the hysteretic response of conventional SWs. 4,26,27 In Girhammar et al, 28 an analytical procedure to quantify the tying-down effect of wood-frame TSWs on the loadcarrying capacity of partially anchored conventional wood-frame SWs was proposed, revealing that TSWs can enhance the lateral in-plane load-carrying capacity of SWs. The extent of improvement diminishes with decreasing wall aspect ratio (e.g., up to a 100% increase for SWs with a 1:2 aspect ratio and up to a 32% increase for SWs with a 1:0.5 aspect ratio).…”
Section: Previous Research On the Influence Of Tswsmentioning
confidence: 99%
“…However, contrary to previous studies, [20][21][22][23] Foliente et al's numerical study 4,26 concluded that TSWs do not impact the hysteretic response of conventional SWs. 4,26,27 In Girhammar et al, 28 an analytical procedure to quantify the tying-down effect of wood-frame TSWs on the loadcarrying capacity of partially anchored conventional wood-frame SWs was proposed, revealing that TSWs can enhance the lateral in-plane load-carrying capacity of SWs. The extent of improvement diminishes with decreasing wall aspect ratio (e.g., up to a 100% increase for SWs with a 1:2 aspect ratio and up to a 32% increase for SWs with a 1:0.5 aspect ratio).…”
Section: Previous Research On the Influence Of Tswsmentioning
confidence: 99%
“…Also, considering the possibility of manufacturing parts of this system in the factory and installing it on site, the speed of implementing the system is high and operating costs are reduced to some extent (Kalantari et al 2020). This system is the best alternative in terms of performance and safer in terms of strength and behavior in comparison with concrete shear walls, and it can be used not only in steel structures but also in concrete structures (Girhammar et al 2017). In terms of comparison with bracing systems and in terms of shear stiffness, this system is stiffer than the stiffest bracing systems, and due to the possibility of making openings anywhere, it has the efficiency of all bracing systems in this regard (Wang, M et al 2017) Research results show that the behavior of the system in the plastic environment as well as its energy absorption is better than bracing systems (Hosseinzadeh, L et al 2017) In this system, due to the wide range of materials and connections, the stresses are adjusted much better than in other strong systems, (Hosseinzadeh, L et al 2017) such as moment frames and various types of braces in which the materials are usually bundled and the connections are concentrated and the behavior of the system is especially more suitable in a plastic environment (Zhi, Q et al,2017).…”
Section: Introductionmentioning
confidence: 99%